Inhibition of Sarco-Endoplasmic Reticulum Ca2+ ATPase Extends the Lifespan in C. elegans Worms - García-Casas, Paloma; Arias-del-Val, Jessica; Alvarez-Illera, Pilar; Fonteriz, Rosalba I.; Montero, Mayte; Alvarez, Javier (Frontiers in Pharmacology, 2018)
The sarco-endoplasmic reticulum Ca2+-ATPase (SERCA) refills the endoplasmic reticulum (ER) with Ca2+ up to the millimolar range and is therefore the main controller of the ER [Ca2+] level ([Ca2+]ER), which has a key role in the modulation of cytosolic Ca2+ signaling and ER-mitochondria Ca2+ transfer. Given that both cytosolic and mitochondrial Ca2+ dynamics strongly interplay with energy metabolism and nutrient-sensitive pathways, both of them involved in the aging process, we have studied the effect of SERCA inhibitors on lifespan in C. elegans. We have used thapsigargin and 2,5-Di-tert-butylhydroquinone (2,5-BHQ) as SERCA inhibitors, and the inactive analog 2,6-Di-tert-butylhydroquinone (2,6-BHQ) as a control for 2,5-BHQ. Every drug was administered to the worms either directly in the agar or via an inclusion compound with -cyclodextrin. The results show that 2,6-BHQ produced a small but significant increase in survival, perhaps because of its antioxidant properties. However, 2,5-BHQ produced in all the conditions a much higher increase in lifespan, and the potent and specific SERCA inhibitor thapsigargin also extended the lifespan. The effects of 2,5-BHQ and thapsigargin had a bell-shaped concentration dependence, with a maximum effect at a certain dose and smaller or even toxic effects at higher concentrations. Our data show therefore that submaximal inhibition of SERCA pumps has a pro-longevity effect, suggesting that Ca2+ signaling plays an important role in the aging process and that it could be a promising novel target pathway to act on aging.